Victims of the Terrorist Attacks in Belgium and Professional Mental Health Aid Barriers: A Qualitative Study - Van Overmeire, Roel; Muysewinkel, Emilie; Van Keer, Rose-Lima; Vesentini, Lara; Bilsen, Johan (Frontiers in Psychiatry, 2021)
Introduction: Terrorist attacks can cause short and long-term stress-reactions, anxiety, and depression among those exposed. Sometimes, professional mental health aid, meaning all types of professional psychotherapy, would be appropriate, but victims often delay or never access mental health aid, even up to a decade after the initial event. Little is known about the barriers terrorist-victims encounter when they try to access professional mental health aid. Method: Using a qualitative design, 27 people exposed to the 22/03/2016 terrorist attack in Belgium were interviewed using half-structured, in-depth interviews, on their experiences with professional mental health aid. A reflexive thematic analysis was employed. Results: Five main barriers for professional mental health aid seeking by victims were found. First, their perception of a lack of expertise of mental health aid professionals. Second, the lack of incentives to overcome their uncertainty to contact a professional. Third, social barriers: people did not feel supported by their social network, feared stigma, or trusted that the support of their social network would be enough to get them through any difficulties. Fourth, a lack of mental health literacy, which seems to be needed to recognize the mental health issues they are facing. Finally, there are financial barriers. The cost of therapy is often too high to begin or continue therapy. Conclusions: This study showed that the barriers for seeking professional mental health aid are diverse and not easily overcome. More mental health promotion is needed, so that there is a societal awareness of possible consequences of being exposed to terrorist attacks, which might result in less stigma, and a quicker realization of possible harmful stress reactions due to a disaster.